Adriaan Hulshoff’s Curaçao: An Analysis of the Novel Dorstig paradijs (1949) - Bant, Willem (Werkwinkel, 2019)
In 1949, the Dutch publishing house A.J.G. Strengholt’s Uitgeversmaatschappij N.V. published the novel Dorstig paradijs. Through the eyes of Evelien van Eerdhuysen, the young, Dutch, female protagonist, author Adriaan Hulshoff presented an image of postwar Curaçao. In general, Dutch reviews of Hulshoff’s novel were quite positive and mentioned, for instance, the realistic representation of the island. Reviews published on Curaçao were very negative. At the moment the novel was published, Curaçao was fully in the news, because of the deliberations about the political status of the Dutch islands in the Caribbean. The question can be raised whether the image of Curaçao presented by Hulshoff was widespread in the Netherlands and representative of the way the Dutch looked at their Caribbean colonial possessions. One of the reasons why the book got much attention had to do with the name of the author who was hiding behind the pseudonym Adriaan Hulshoff. Most probably it was the well-known female writer Jo van Ammers-Küller, who after the Second World War, was banned from publishing because of collaborating with the Germans.